2023
DOI: 10.1039/d3bm01275a
|View full text |Cite
|
Sign up to set email alerts
|

Nanocarriers for gene delivery to the cardiovascular system

Ling-Xin Shi,
Xiu-Ran Liu,
Ling-Yue Zhou
et al.

Abstract: Cardiovascular diseases have posed a great threat to human health. Fortunately, gene therapy holds great promise in the fight against cardiovascular disease (CVD). In gene therapy, it is necessary to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 162 publications
(198 reference statements)
0
2
0
Order By: Relevance
“…INPs are synthesized from inorganic particles and biodegradable polycations [105], including metals, metal oxides, carbon materials, and magnetic nanoparticles such as superparamagnetic iron oxide NPs [106]. Their inherent biocompatibility, stability, resistance to microbial degradation, and efficient delivery contribute to their clinical significance [107].…”
Section: Inorganic Nps (Inps)mentioning
confidence: 99%
“…INPs are synthesized from inorganic particles and biodegradable polycations [105], including metals, metal oxides, carbon materials, and magnetic nanoparticles such as superparamagnetic iron oxide NPs [106]. Their inherent biocompatibility, stability, resistance to microbial degradation, and efficient delivery contribute to their clinical significance [107].…”
Section: Inorganic Nps (Inps)mentioning
confidence: 99%
“…6 To achieve this goal, researchers have been exploring more efficient and safe genes and gene vectors. 7,8 The group's previous study found that the human C2H2-type zinc finger protein gene ZNF580 is involved in the transcriptional regulation of angiogenesis. 9 In human umbilical vein endothelial cell (HUVEC) lines, overexpression of the ZNF580 gene promotes the expression of MMP-2 and VEGF and enhances the migratory and proliferative activities of HUVECs.…”
Section: Introductionmentioning
confidence: 99%